2017
DOI: 10.9734/ijbcrr/2017/32954
|View full text |Cite
|
Sign up to set email alerts
|

Production and Properties of Probioticic Soursop Juice Using Pediococcus pentosaceus LBF2 as Starter

Abstract: Aims: Production of probiotic soursop juice and determination of properties of the juice samples for 3 weeks of storage at 4°C. Study Design: To determine the properties of soursop juice produced using Pediococcus pentosaceus LBF2 as starter culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The viable cell counts of Lb. casei in the P.C.A.B treatments were higher than 10 6 cfu/ml after 3 weeks of cold storage and this fact was confirmed by (Akpeji et al, 2017). Shah (2001) added that it is important to have significant number of viable lactic acid bacteria (L.A.B) in the product for maximum health benefits.…”
Section: Resultsmentioning
confidence: 80%
“…The viable cell counts of Lb. casei in the P.C.A.B treatments were higher than 10 6 cfu/ml after 3 weeks of cold storage and this fact was confirmed by (Akpeji et al, 2017). Shah (2001) added that it is important to have significant number of viable lactic acid bacteria (L.A.B) in the product for maximum health benefits.…”
Section: Resultsmentioning
confidence: 80%
“…The pulp was obtained by blending with sterile distilled water in a ratio of 1:2 (w/v, pulp/water). Soursop juice was extracted by filtering with a sterile muslin cloth (Akpeji et al, 2017). Next, the extracted juice was poured into a sterile bottle and pasteurized at a temperature of 79°C for 69 seconds (Abbo et al, 2006).…”
Section: Preparation Of Soursop Juicementioning
confidence: 99%
“…The TSS of the soursop juice incorporated with emulsified L. plantarum NBRC 3070 during storage was determined by using a hand refractometer (Abbe, Japan), which was based on the method proposed by Akpeji et al (2017).…”
Section: C) Total Soluble Solidmentioning
confidence: 99%
“…These results were similar to De Roeck et al (2009) who reported that control samples (unpasteurized mango juice) were spoilt during the first week of storage at ambient temperature 30±2°C. This might be due to the presence of enzymes such as pectinase and vegetative microorganisms including bacteria, molds and yeasts in unpasteurized samples that could ferment and cause spoilage (Akpeji et al, 2017).…”
Section: Tpc Of Honey Beveragesmentioning
confidence: 99%